An unconventional approach in investigating wettability contact angle measurement in shale resources - Almudhhi, S. (Taylor and Francis Ltd., 2021)
Wettability measurement is important in production development to newly discovered as well as mature reservoirs. Evaluating the wettability is exceptionally important (for its significant-yields in hydrocarbon quantities) in oil and gas production schemes for newly discovered reservoirs such as shale reservoirs and other unconventional plays. Shale wettability has its unique fluid-mineral distribution relationships, which makes both pore morphology as well as mineral composition very significant factors controlling its wettability. The complex shale physical, chemical, and crystollgraphical constituentâs mineralogy as well as its physical pore morphology heterogeneity can complicate the wettability measurement further inside the pore structure fabrication, and hence the ultimate oil/gas recovery. The main objective of this study is to investigate the complexity of heterogeneous mineral structure of shale as well as its complex pore structure and its attributes toward the unconventional imaging method of wettability contact angle measurement. Â© 2021 Taylor & Francis Group, LLC.